NEGATIVE LABELS AGAINST WOMEN IN REI KIMURA'S BUTTERFLY IN THE WIND: A DECONSTRUCTION ANALYSIS ON THE CHARACTER OF “TOJIN” OKICHI - Shita Dewi Ratih Permatasari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
Women have often been the ideal target to be culturally and socially constructed within a patriarchal society. This serves as a form of gender inequality that mostly brings harm to them. In this analysis, through men’s domination and power over women, these negative social attributes were intentionally as well as politically constructed to put women as ‘deviant’. Applying Derrida’s deconstruction theory, the negative labels could be deconstructed into positive social attributes through a critical analysis on the main character, Okichi in the novel Butterfly in the Wind written by Rei Kimura. The finding posits that Okichi labeled as a “comfort woman” or “mistress” by the Shimoda’s society can be re-interpreted or given a new positive meaning as heroic action which was taken to save her family and country’s dignity